Lot-to-lot consistency, immunogenicity, and safety of an inactivated SARS-CoV-2 vaccine (CoronaVac) in healthy adults: A randomized, double-blind, phase IV trial - Dandan Zhu; Yuansheng Hu; Zhiwei Jiang; Tuantuan Yang; Kai Chu; Hengming Zhang; Jialei Hu; Xing Meng; Zhijun Tan; Jingliang Wu; Xiaojuan Lian; Changgui Li; et al. (Taylor & Francis Group, 2022)
Previous phase I to III clinical trials have shown that the inactivated SARS-CoV-2 vaccine namely CoronaVac has good efficacy, safety, and immunogenicity. This phase IV trial aims to evaluate the lot-to-lot consistency, immunogenicity, and safety on a commercial scale in healthy adults, which could provide data to support stable manufacturing. In this single-center, randomized, double-blind study, 1,080 healthy adults aged 26-45 years were randomly assigned into three groups to receive one of three lots of vaccines. All subjects received two doses of CoronaVac with an interval of 28 days. Serum samples were collected before the first dose and 28 days after the second dose to assess the immunogenicity. Solicited local and systemic adverse events (AEs) within 7 days and unsolicited AEs within 28 days after each dose of vaccination were recorded. A total of 1,039 participants completed the study and were included in the per-protocol set (PPS). The GMTs were 75.2 (68.5,82.6), 65.0 (59.0,71.7), and 65.3 (59.4,71.8), respectively, and the seroconversion rates of neutralizing antibody were all higher than 98%. The GMT ratios of each pair of lots were 1.16 (1.01,1.32), 1.15 (1.01, 1.32), and 0.99 (0.87, 1.14), respectively, meeting the immunological equivalence criteria. The incidence rates of adverse reactions (ARs) were 19.17%, 13.89%, and 18.33%, with no statistical difference. The ARs were all in grade 1 and grade 2, with incidences of 15.46% and 2.50%. Non-vaccine-related serious adverse events (SAEs) were reported. These results showed robust lot-to-lot consistency, immunogenicity, and safety. The stable production indicated that CoronaVac is suitable for large-scale use.Trial registration number: NCT04894227 (ClinicalTrials.gov).